PENGARUH PERSEPSI, MEKANISME PEMBAYARAN DAN KUALITAS PELAYANAN TERHADAP KEPATUHAN WAJIB PAJAK PADA KPP PRATAMA BATAM SELATAN - Sitio, Evlin Uli Carolin; Poniman, Poniman (LPPM Universitas Putera Batam, 2025)
The purpose of this study is to evaluate the effect of the independent variables on the dependent variable. In this study, the independent variables include perception, payment mechanism, and service quality. Meanwhile, the dependent variable is compliance. Compliance is a process that involves administrative steps and is required to fulfill tax obligations set out in tax regulations. The population studied was taxpayers registered in Batam, while the sample was taken using the Slovin formula with a 10% margin of error percentage. This study uses a quantitative approach is used as a testing method. Data collection was carried out using a questionnaire given to 100 respondents and then analyzed using a Likert scale. The collected data was processed with the help of SPSS. The linear regression analysis process in this study aims to understand the interaction between variables. The research findings show that perception has a positive and significant influence on taxpayer compliance, the payment mechanism also affects positively and significantly, as well as the quality of service which has a positive and significant impact on compliance.. The f test also shows that perception, payment mechanism, and service quality have a positive and significant influence on taxpayer compliance.